Three Strongly Coupled Allotropes in a Functionalized Porous All-Carbon Nanocomposite as a Superior Anode for Lithium-Ion Batteries - Deng, X.; Zhao, B.; Sha, Y.; Zhu, Y.; Xu, X.; Shao, Zongping (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2016)
A 3D hierarchically porous architecture built from three different carbon allotropes (graphene, carbon nanotubes, and chitosan-derived porous carbon) has been prepared by using a simple molten-salt synthesis method. The resulting all-carbon nanocomposite is strongly coupled and functionalized with high heteroatom doping (N: 5.3% and O: 13.5%), which has a high specific surface area of 1614m2g-1. Based on the unique characteristics mentioned above, and the positive synergistic effects of the allotropes, the nanocomposite exhibits favorable features as an electrode for lithium-ion batteries. An outstanding reversible specific capacity of 1448mAhg-1 is achieved at 100mAg-1. Even after 200 cycles at 1000mAg-1, a high capacity of 749mAhg-1 is still retained. The remarkable electrochemical performance makes this 3D functionalized porous all-carbon nanocomposite a promising anode material. This work further opens a novel avenue to develop next-generation all-carbon electrochemical materials.